Guatemala : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that following three years of sluggish economic growth, activity in Guatemala improved somewhat in 2004, with real GDP rising by 2 3/4 percent, but consumer price inflation drifted upward to more than 9 percent. Monetary policy is being geared to reducing inflation to the 4-6 percent range. The exchange system is flexible, but the central bank has intervened in the foreign exchange in 2004 to contain the appreciation of the quetzal against the U.S. dollar. In January 2005, a rules-based mechanism for interventions was introduced.